2024
DOI: 10.1590/s1677-5538.ibju.2024.0084
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram to predict the absence of clinically significant prostate cancer in males with negative MRI

Masatomo Kaneko,
Atsuko Fujihara,
Tsuyoshi Iwata
et al.

Abstract: Purpose: To create a nomogram to predict the absence of clinically significant prostate cancer (CSPCa) in males with non-suspicion multiparametric magnetic resonance imaging (mpMRI) undergoing prostate biopsy (PBx). Materials and Methods:We identified consecutive patients who underwent 3T mpMRI followed by PBx for suspicion of PCa or surveillance follow-up. All patients had Prostate Imaging Reporting and Data System score 1-2 (negative mpMRI). CSPCa was defined as Grade Group ≥2. Multivariate logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Dr. Kaneko and collegues from USA and Japan performed in page 319 ( 6 ) the paper that is the cover of the present edition. This Interesting paper is about a nomogram to predict the absence of clinically significant prostate cancer in males with negative MRI and concluded that this nomogram facilitates evaluating individual probability of clinically significant prostate cancer (CSPCa) on prostatic biopsy (PBx) in males with PIRADS 1-2 mpMRI and may be used to identify those in whom PBx may be safely avoided.…”
mentioning
confidence: 99%
“…Dr. Kaneko and collegues from USA and Japan performed in page 319 ( 6 ) the paper that is the cover of the present edition. This Interesting paper is about a nomogram to predict the absence of clinically significant prostate cancer in males with negative MRI and concluded that this nomogram facilitates evaluating individual probability of clinically significant prostate cancer (CSPCa) on prostatic biopsy (PBx) in males with PIRADS 1-2 mpMRI and may be used to identify those in whom PBx may be safely avoided.…”
mentioning
confidence: 99%